2020
DOI: 10.4236/jss.2020.810015
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Linguistic Landscape of the Cultural Heritage Sites and Tourist Spots in Bangladesh

Abstract: Language choices in colonized societies are shaped by a combination of local, national, and global forces as well as historical, political, religious and economic factors. This is particularly true in Dhaka and Cox's Bazar. Adopting an ethnography, this study attempts to investigate the intersection of language practices and ideologies by examining the language use and language choices displayed in cultural heritage sites and tourism scenic spots both in public and private multilingual signs. Data are collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…Multilingualism in the linguistic landscape is defined as the use of multilingual signs which include more than two languages. This finding matches earlier studies that documented multilingualism in linguistic landscapes in multiple contexts (Belles-Calvera, 2019;Coluzzi, 2020;Dong et al, 2020;Husin et al, 2019;McKiernan, 2019;Woo & Nora Riget, 2020), where several factors were revealed as the reason for this phenomenon. The most obvious reason for this situation could be the multi-ethnic composition or a particular area, as suggested by (McKiernan, 2019).…”
Section: Multilingualism In the Tourist Spacesupporting
confidence: 91%
See 1 more Smart Citation
“…Multilingualism in the linguistic landscape is defined as the use of multilingual signs which include more than two languages. This finding matches earlier studies that documented multilingualism in linguistic landscapes in multiple contexts (Belles-Calvera, 2019;Coluzzi, 2020;Dong et al, 2020;Husin et al, 2019;McKiernan, 2019;Woo & Nora Riget, 2020), where several factors were revealed as the reason for this phenomenon. The most obvious reason for this situation could be the multi-ethnic composition or a particular area, as suggested by (McKiernan, 2019).…”
Section: Multilingualism In the Tourist Spacesupporting
confidence: 91%
“…The first theme concerns the dominant language in the linguistic landscapes analysed by these studies. In multiple contexts of the studies, the English language has emerged as the primary language used for the observed linguistic landscapes (Darmawan, 2018;Da Silva et al, 2021;Dong, 2020;Fakhiroh & Rohmah, 2018;Sibarani et al, 2021;Solikha et al, 2020;Thongtong, 2016). Some of these studies also reported that the English language had dominated the observed linguistic landscapes compared to local or other languages (Khazanah & Kusumanungutri, 2021;Koschade, 2016;Prasert & Zilli, 2019;Rong, 2018;Ruzaite, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the presence of errors in a small percentage of signs highlights the evolving attention to language use or potential foreign influence, aligning with discussions on language learning and societal development (Cenoz & Gorter, 2008;Gorter el al., 2021;Li et al, 2020). These findings contribute to the understanding of how linguistic landscapes impact urban identity, tourism, and economic activities (Cenoz & Gorter, 2008;Cenoz & Gorter, 2009;Dong et al, 2020;Hasni et al, 2022;Farfán Pacheco, 2020;Leeman & Modan, 2010;Li et al, 2020;Rola, 2019;Shohamy et al, 2010;Shohamy & Waksman, 2009;). The distinct distribution of businesses and services in different areas of the city further emphasizes the unique linguistic dynamics in Cuenca (García et al, 2017).…”
Section: Discussionmentioning
confidence: 82%
“…In fact, Kallen (2023) argued that "the LL can be contained by public space, but […] the language display of the LL in fact creates the public space" (p.80). In this sense, linguistic landscapes could have a direct influence on the activities that take place in public spaces, namely, on tourism (Hasni et al, 2022;Dong et al, 2020), the economy (Cenoz & Gorter, 2009;Järlehed et al, 2023), the visual organization of the cities (Farfán Pacheco, 2020; Leeman & Modan, 2010;Rola, 2019;Shohamy et al, 2010), and language learning (Gorter et al, 2021;Hatoss, 2023;Li et al, 2020) Public areas that have language related to tourism are places where people from different cultural and linguistic backgrounds are found. The display of different languages in these areas portrays this diversity, which contributes to a sense of inclusivity and fosters a richer cultural environment.…”
Section: Introductionmentioning
confidence: 99%
“…Kontestasi bahasa yang terdapat di Candidasa memiliki kemiripan dan perbedaan dengan temuan Dong et al (2020) tentang pemetaan LL beberapa tempat wisata di Bangladesh. Persamaan yang terlihat adalah tentang kebijakan bahasa nasional di Indonesia dan Bangladesh menyebabkan banyaknya tanda luar ruang yang memakai bahasa nasional masing-masing.…”
Section: Tabel 5 Tanda Luar Ruangunclassified